MANET在空间复用随机模型下的平均洪泛距离研究 - 胡细; 王汉兴; 赵飞 (上海大学学报（英文版）, 2007)
O29; The flooding distance is an important parameter in the design and evaluation of a routing protocol, which is related not only to the delay time in the route discovery, but also to the stability and reliability of the route. In this paper,the average flooding distance (AFD) for a mobile ad hoc network (MANET) in a random graph model was given based on the dynamic source routing (DSR) protocol. The influence of spatial reuse on the AFD was also studied. Compared with that in the model without the spatial reuse, the AFD in the model with the spatial reuse has much smaller value, when the connetivity probability between nodes in the network is small and when the number of reused times is large. This means that the route discovery with the spatial reuse is much more effective.